Modules of Organizational and Technical Systems for Solving Problems of Adaptation in a Rapidly Changing Environment - A. Mikryukov; V. M. Trembach; A. V. Danilov (Открытое образование (Москва))
Purpose of research. The aim of the research is to form modules of organizational and technical systems (OTS) using a cognitive approach to solve problems of adaptation of cyberphysical systems. Currently, there is a rapid development of elements of the Internet of things. New tasks related to self-organization and adaptation in a rapidly changing external environment are brought to the fore. These tasks occur when new elements appear in the telecommunications computer network, they fail, change the mode, new tasks occur, etc. To work out these tasks, the possibilities of approaches to support and decision-making such as situational, cognitive, and semiotic are considered. The authors consider the cognitive approach in more detail. Within the framework of the cognitive paradigm, the article describes the use of the cognitive approach for solving problems of adaptation of cyberphysical systems. To solve this problem on the basis of an agent-based approach, the structure of a cyberphysical system with the possibility of adaptation is presented and the functions of its agents are described. The main stages of solving problems of adaptation of cyberphysical systems are presented. An adaptation algorithm using the planning mechanism is presented. The demo example shows a knowledge base for solving the problem of adapting cyberphysical systems using a cognitive planning mechanism.Materials and methods of research. New approaches and methods are required to address adaptation issues in planning. The cognitive approach is one of the developing directions in solving many problems of the Internet of things. One of these tasks is the ability to adapt OTS modules in a rapidly changing external environment based on the planning mechanism. To solve the planning problem, we use the algorithm described by Aristotle more than 2,350 years ago and implemented in the GPS program. This algorithm can be considered the first description of the cognitive mechanism that a person uses. The knowledge base uses an integrated approach to knowledge representation. When developing OTS modules, an agent-based approach was used to solve the problem of adaptation.Results. The existing and developing approaches and methods for decision support and decision-making are considered for decisionmaking in newly emerging situations in OTS modules. The main provisions of such significant approaches as situational, cognitive and semiotic are presented. A cognitive approach to the adaptation of intelligent systems is proposed. The solution of the problem of adaptation of cyberphysical systems is considered within the framework of the cognitive paradigm. The structure of a cyberphysical system capable of solving adaptation problems is shown. The functions of OTS modules based on agent-oriented technology are described. A description of the adaptation algorithm using the cognitive planning mechanism is given. The main stages of solving problems of adaptation of cyberphysical systems are presented. A demo example of solving the problem of adaptation by a cyberphysical system-a cooking robot – is shown.Conclusion. Using the modular architecture of an intelligent system allows you to solve many problems. One of these tasks is to configure elements of the Internet of things when they deviate from their main function. The planning mechanisms proposed for parametric adaptation can be repeatedly applied in OTS modules as separate agents. This approach is relevant for elements of the Internet of things. In the case of expanding the functionality of the OTS modules of Internet of things, it is advisable to apply machine learning with fixing the results in the knowledge base of planning agents.